Development of AR and VR Home Brochure Applications PT. Griya Pantura Mandiri Kendal Based on Android - Muhammad Khoiril Anaam; Ahmad Zainudin (University of Science and Computer Technology, 2024)
Based on observations, promotional media used at PT. Griya Pantura Mandiri Kendal is a brochure. The effectiveness of the brochure as a promotional media tool so far has not been enough to have an impact on the level of understanding of information and product visualization by the user. This research offers a solution to the use of Augmented Reality (AR) and Virtual Reality (VR) technology as an attractive visualization media promotion tool, users can see the object of the house according to the type scanned using an Android device, in addition they can visit the house according to that type in advance with virtual Android devices. The validity value of media experts was 3.8 which was declared feasible, while the validity value of material experts was 4 which was declared feasible, and product trials by users increased the understanding of information and visualization in the brochure from 28% initially to 88%. Based on the results of observations, the promotional media used at PT. Griya Pantura Mandiri Kendal is a brochure. The effectiveness of brochures as a promotional media tool so far has not had enough impact on the level of understanding of information and product visualization by users. This research offers a solution for utilizing Augmented Reality (AR) and Virtual Reality (VR) technology as an attractive promotional media visualization tool for users. can see house objects according to the type scanned using an Android device, apart from that they can visit houses according to that type first virtually with an Android device. The validity value from media experts was 3.8, which was declared feasible, while the validity value from material experts was 4, which was declared feasible, and product trials by users increased understanding of information and visualization in brochures from initially 28%, increasing to 88%.